Accelerating India : 7 years of Modi government - Alphons, K.J. (ed.); Doval, Ajit (fwd.) (Gurugram Oak Bridge Publishing, 2021)
Accelerating India: 7 Years of Modi Government qualitatively and quantitatively evaluates the policies of the government in the last 7 years and their impact on the citizens and the nation. The book focuses on twenty-five key sectors, including Education, Economy, Industry, Infrastructure, Digital Revolution, Energy, Environment, Health, Foreign Policy, Agriculture, Rural Development, Sanitation, and Social Justice & Empowerment.
Keywords: Editor as a civil servant; Indian Administrative Services; Politics and government; Economic policy; Social policy; Narendra Modi; India